BASULIFOR PROBIOTIC SUPPLEMENT, ITS IMPACT ON BODY AND PRODUCTIVITY OF YOUNG QUAILS - I. A. Alekseev; V. G. Semenov; D. A. Baimukanov; V. A. Alekseev; N. V. Evdokimov; A. V. Yakimov; A. V. Obukhova (Scientific Journal of Pedagogy and Economics, 2019)
For the first time, on the basis of comprehensive research, the feasibility of using Basulifor domestic probiotic supplement in the growing technology of quail was scientifically grounded and experimentally proved. The feed additive contributed to an increase in the number of erythrocytes in the blood of birds by 5.20-5.69% (P<0.05), hemoglobin concentration - by 3.80-4.48 (P<0.05), the amount of total protein in serum blood - by 3.89-6.66% (P<0.05), gamma globulins - by 7.29-8.03% (P<0.01), class A immunoglobulins - by 11.50-15.30% (P<0.01), IgM - by 7.14-10.70% (P<0.01), IgG - by 6.54-6.80% (P<0.01), birds' preservation - 93.0 to 97.34% (P<0.01).It was established that the 1st and 2nd experimental groups quails surpassed their peers in control in live weight by 5.30 and 10.50 g (P<0.05), the average daily gain was 0.08 and 0.17 g. Killing yield of quails against the background of the use of feed supplement was higher by 1.97% and 3.76% (P<0.05) rather than in the control group. Quail meat samples of the 1st experimental group treated with ozone-air mixture at a dose of 5 mg/m3, without losing their quality indicators, remained for 18.00±0.36 days, and in the 2nd experimental group when processing meat samples with ozone in a dose of 10 mg/m3 - for 24.00±0.53 days. Compared with the control batch of meat, these indicators in the experimental groups were higher by 12.0 and 18.0 days (P<0.01). The novelty of the obtained data is confirmed by the fact that for the first time the feasibility of correcting the morphological, biochemical, and immune status of the body, increasing the preservation, productivity and quality of meat products of young quails by using Basulifor probiotic feed additive has been proved.